Progressive collapse and robustness of modular high-rise buildings. Issue 3 (25th November 2022) - Thai, Huu-Tai; Ho, Quang Vu; Li, Wenqian; Ngo, Tuan
Abstract: Contrary to conventional buildings, the structural robustness of modular high-rise buildings has not been studied due to the lack of the numerical and experimental studies and design guides. To gain a better understanding of their structural robustness against progressive collapse, this paper investigates the robustness of modular high-rise buildings using the alternative load path method with nonlinear time-history analysis. A numerical model of a typical modular tall building subjected to a corner module removal scenario was developed to explore its typical response, resistance mechanism and progressive collapse. A comprehensive parametric study was then performed to examine the effects of a wide range of parameters (e.g. column cross-section, inter-module connection and bracing system) and configurations on the progressive collapse and structural robustness of modular buildings. The result showed that bracing systems can enhance the structural robustness effectively by sharing redistributed loads and restraining structural members. The removal of corner members is more critical because there are limited adjacent members for sharing the redistributed loads. Inter-module connections should provide adequate strength to develop more alternative load paths when extreme events occur. Finally, design recommendations for improving the robustness of modular buildings were also proposed based on the findings from the parametric study.